Catching reef fish using floating traps. Issue 1 (October 2021) - Palo, Mahfud; Najamuddin; Assir Marimba, Andi; Musbir; Ainun Jurdillah, Nur
Abstract: Floating traps are one of the new fishing gear innovations in Indonesia which are tested to catch reef fish because all this time reef fish are caught using traps which are operated on the bottom of the waters. The floating traps are targeted to be able to catch coral pelagic fish, namely reef fish that always cluster on coral reefs, for example fusiliers ( Caesio sp). which is usually the target of capture through the use of bombs (blast fishing). So far, floating traps have been used to catch salmon and other pelagic fish such as scads ( Decapterus sp) and flying fish ( Cypselurus sp). This research is a basic research which aims to make floating traps as an alternative tool for catching fusiliers. This research was conducted in the waters around Pajenekang Island (Spermonde Islands) from September to ecember 2020. A total of 2 traps (2.4 × 1 × 1 m) were operated around the coral reef at 2 positions, namely at the bottom, and at 2 m from the bottom of the sea. The results showed that there was no difference in catch productivity between traps that were operated at the bottom of the water and traps that were operated at a position 2 m from the bottom of the water. The only difference is in the type of catch, namely grouper (Serranidae) and shrimp (Penaeidae) which are only caught in the bottom of the water and squid (Loliginidae is only caught in the trap 2 m from the bottom of the sea. This shows that reef fish have a vertical distribution from the bottom to the water column. The types of fish caught are Apogonidae, Chaetodontidae, Ephippidae, Holocentidae, Labridae, Loliginidae, Monacanthidae, Nemipteridae, Pempheridae, Penaeidae, Plotosidae, Pomacentridae, Scaridae, Serranidae, Siganidae, Tetraodontidae.